Pengaruh Penambahan Bungkil Inti Sawit Terhadap Pertumbuhan dan Aktivitas Enzim Pencernaan Pada Ikan Gurami (Osphronemus gouramy) - Inez, Sthefanie Gita; Kusdianto, Heru; Reynalta, Ricko; Nikhlani, Andi; Ma’ruf, Mohamad (Jurnal Akuakultur Sungai dan Danau, 2024)
The production of aquaculture in East Kalimantan Province in 2023 was recorded at 162,124 tons. This data indicates that the need for fish feed (pellets) is also very large. Meanwhile, it is known that the price of feed continues to climb. This study aims to observe the effect of the use of palm kernel meal, as an alternative feed ingredient, which is fermented using EM4 with different doses on the activity of digestive enzymes and the growth of gourami fish weight. The doses of EM4 used were 0 mL/kg (P1), 4 mL/kg (P2), and 8 mL/kg (P3). Based on the results of the analysis of variance, it was known that the inclusion of fermented palm kernel meal significantly (P<0.05) affected activities of amylase, protease, and lipase enzymes. The highest value of digestive enzyme activity was observed in P2 which produced amylase enzyme activity of 6.31 U/mL, protease 0.46 U/mL, and lipase 0.38 U/mL, and then followed by P3 which produced amylase enzyme activity of 4.76 U/mL, protease 0.39 U/mL, and lipase 0.35 U/mL. The lowest value of activity was observed in gourami treated with P1 which produced amylase enzyme activity of 4.048 U/mL, protease 0.36 U/mL, and lipase 0.31 U/mL. Analysis of variance also showed that fermented palm kernel meal had a significant effect (P<0.05) on the weight growth of giant gourami. The highest weight gain was produced by P3 (2.16 g), then followed by P2 (1.79 g), and P1 (1.21 g). The best feed conversion was produced by P2 (2.32), followed by P3 (2.94), and P1 (3.28).